Influência do risco de base na comercialização da soja em Mato Grosso - Feuser, Carlos Eduardo Prado (2014)
Considering the high representation of soybeans in economic activity in the State of Mato Grosso, this study examines the risk that arises from the search for protection against fluctuations in future trading prices of soybeans. The demand for such protection makes the agents who sell soybeans are used in hedging transactions are available in the commodities and futures. However, due to the different between the physical and futures markets geographical location, this protection may not be perfect, giving room for the emergence of a new venture, called basis risk. It is understood that the basis is the difference between the price on the spot market and futures price of a commodity, basis risk is the risk that arises from the uncertainty about the behavior of the base time soon. Therefore, to understand the risks involved in the marketing of production, as well as risks arising from hedging transactions are highly relevant to the Mato Grosso economy because, variations in market prices may lead farmers and other players in this market to incur losses. In this sense, a discussion of the theory of risk pricing, will be present as well, which the operations available on commodity exchanges to hedge against fluctuations in future prices and finally evaluate the performance of the base from the viewpoint agents of mato Grosso agribusiness. In this work we analyze the behavior of the base period 2009 to 2014 for the cities of Sorriso-MT, New Mutum-MT and MT-Sapezal by applying descriptive statistics, as well as graphical analysis. The purpose of this study is to understand the behavior of the base over time, identifying the existence of patterns of gains or losses for the agents that carry out hedging operations can take advantage of the information and thus favor the achievement of better results in marketing soybeans in Mato Grosso.